Factors related to vaccines for both patients exposed with rabies and dogs - Lam Quy Ngo; Chuyen Van Nguyen; Khoa Ba Tran; Ba Van Nguyen; Loi Ba Cao; Trung Hoang Nguyen; Trang Thi Thu Nguyen; Luong Van Hoang (Revista Cubana de Medicina Militar)
Introduction: Rabies is a viral disease that can be transmitted from animals to humans. All warm-blooded animals, including humans, can host rabies's virus. Vaccination of dogs is an effective method of preventing rabies in humans. Objectives: To evaluate knowledge, attitudes and practices towards rabies prevention and factors related to vaccines for both patients exposed with rabies and dogs. Methods: A cross-sectional descriptive study, using the questionnaire on rabies prevention by interviewing 1 484 households. Multivariable logistic regression analysis was used to identify factors related to vaccines for both patients exposed to rabies and dogs. Results: Of all 67.32 % of the people surveyed with high knowledge, only 43.8 % and 31.47 % were assessed as having a good attitude and practice. Interviewees with poor knowledge and practice are independently related to low-rate vaccines provision for pets. Factors associated with low vaccination rates after pet bites were poor attitudes and practices. Conclusion: People with a high level of education, knowledge and practice, the rabies vaccination rate on pets is high. People with good attitudes and practices had a high rate of rabies vaccination after being bitten by an animal.